2019
DOI: 10.15578/iaj.14.1.2019.7-14
|View full text |Cite
|
Sign up to set email alerts
|

POPULATION GENETIC STRUCTURE OF SPINY LOBSTERS, Panulirus homarus AND Panulirus ornatus, IN THE INDIAN OCEAN, CORAL TRIANGLE, AND SOUTH CHINA SEA

Abstract: Populations of spiny lobsters worldwide are threatened by overfishing, while its supply from aquaculture is currently insufficient to meet the market demand. This current study investigated the genetic structure of two economically important spiny lobsters, P. homarus and P. ornatus sourced from the Indian Ocean and South China Sea. Fragments of the cytochrome oxidase subunit-I (COI) gene of the mitochondrial DNA of 71 P. homarus and 42 P. ornatus collected from 6 and 5 fish landing sites in Indonesia, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…In general, scalloped spiny lobsters from the Indonesian population, based on FST, showed higher differentiation than those from the Omani population, with FST values ranging from 0 to 0.0021. This nding contradicts previous results that showed no differentiation in scalloped spiny lobsters from Indonesia, which were evaluated using mitochondrial DNA 10 .…”
Section: Evidence Of Population Differentiation Reveal By Genomic Inf...contrasting
confidence: 99%
See 3 more Smart Citations
“…In general, scalloped spiny lobsters from the Indonesian population, based on FST, showed higher differentiation than those from the Omani population, with FST values ranging from 0 to 0.0021. This nding contradicts previous results that showed no differentiation in scalloped spiny lobsters from Indonesia, which were evaluated using mitochondrial DNA 10 .…”
Section: Evidence Of Population Differentiation Reveal By Genomic Inf...contrasting
confidence: 99%
“…However, limited information is available regarding the population structure of scalloped spiny lobsters in Indonesia has been reported. Mitochondrial DNA and microsatellite markers have been reported, but it has been concluded that there is no evidence of a structured population of scalloped spiny lobsters in Southeast Asia 9,10 . This nding has relies on the use of better molecular markers, as Al-Breiki et al, 12 successfully described the evidence of a structured population of scalloped spiny lobsters on the coast of Oman using genome-wide SNP markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many examples of maintaining population connectivity through the dispersal of larvae, such as the main currents flowing along the Atlantic coast of Iberia could have been responsible for maintaining connectivity of populations of Patella rustica through occasional larval transport across a considerable stretch of inhospitable habitat (Ribeiro et al, 2010); Two economically important spiny lobsters, Panulirus homarus and Panulirus ornatus show no genetic differences from the western Indian Ocean to the Indo-Malay archipelago, because larval stage of lobster species had to go through a long floating state (Permana et al, 2019). Contrary to species with long planktonic period, species with short planktonic larval period can show strong population structure, such as the clam Macridiscus multifarius, which planktonic larval stage is about 10 days, high level and significant FST values were obtained among the different localities of M. multifarius on the basis of either COI or 12S rRNA gene, indicating a high degree of genetic differentiation among the populations (Ye et al, 2015).…”
Section: Discussionmentioning
confidence: 99%